Novel insight into the correlation between hernia orifice of cystocele and lower urinary tract function: a pilot study - Takeya Kitta; Hirokazu Abe; Huang Ting-wen; Masahiro Fujikawa; Minoru Nakazono; Taiki Sasa; Yukiko Doi; Sari Toki; Daigo Okada; Atsuhiko Ochi; Koichiro Suzuki; Yasuhide Kitagawa; et al. (BMC, 2022)
Abstract Background It has been hypothesized that women with significant pelvic organ prolapse (POP), particularly of the anterior vaginal wall, may have voiding dysfunction (VD). Although the VD mechanism due to cystocele is not fully understood, different vaginal compartments have rarely been closely examined. This study attempted to further elucidate the correlation between POP and VD through a new subgroup classification using cystoscopy. Methods This study reviewed clinical records of 49 women who underwent cystocele repair. All patients were scheduled for laparoscopic sacrocolpopexy, preoperatively underwent uroflowmetry and postvoid residual urine volume (PVR) measurement, and completed pelvic floor function questionnaires. Bladder examination by cystoscopy was additionally performed using the lithotomy position with the Valsalva maneuver. Results Subjects were divided into four groups according to hernia orifice presence determined by cystoscopy, which included the trigone type, posterior wall type, trigone and urethra type, and trigone and posterior wall type. The posterior wall type had statistically higher PVR values versus the trigone and posterior wall type (P = 0.013). The posterior wall type had statistically lower values for average urine flow rate versus the urethra and trigone type (P = 0.020). There were no significant differences noted in the pelvic floor function questionnaires among the four groups. Conclusions A new bladder defect classification based upon hernia orifice location was associated with lower urinary tract function. Posterior wall hernia presence caused significant voiding function deterioration. This new subgroup classification, which can more clearly identify and indicate bladder function, is also comparable among patients.